PERBANDINGAN LAYANAN GRATIS CHATGPT, GEMINI, DAN DEEPSEEK DALAM PENYUSUNAN PROPOSAL SKRIPSI: STUDI EKSPERIMEN PROMPT. - Sahidin; Ilhan Fauzan; Romadhon Haris Alfian; Fathan Ramadhan; Ahmad Nursodiq (Journal of Research and Publication Innovation, 2025)
This research aims to compare the free services of three AI platforms—ChatGPT, Gemini, and DeepSeek—in assisting undergraduate students in developing thesis proposals. The comparison was carried out using a unified prompt: "Create a structure for a thesis proposal titled 'Development of Academic Information System for University XXX Based on Website Using Waterfall Method'." The outputs were analyzed qualitatively based on completeness of structure, relevance to the topic and methodology, use of academic language, and coherence. The results show that ChatGPT tends to produce the most complete and structured academic response, Gemini provides fast and concise output with a fact-based orientation, and DeepSeek focuses on technical details. These findings can guide students in selecting the most appropriate AI tool to support academic writing tasks.